Dinamika Layanan Perpustakaan di Era Digitalisasi - Sudirman, Sudirman; Utami, Fadilah Risqy; Putri, Nadia Esa (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2023)
The existence of a library is essential in maintaining consistent implementation of policies in the education sector. Libraries as facilities and infrastructure for serving literature needs and learning processes to support the nation's intelligent life process. In the current era of digitalization, as a form of progress in information and technology, it has made it easy for readers to search for knowledge quickly. The need for reading sources and literature can be obtained in an instant without leaving the place at the same time. With the easy accessibility of information, data, recordings or perhaps books created by humans digitally, libraries are increasingly becoming a means of obtaining information. When people search for information or knowledge in digital records, the library function is running. Users who obtain information, knowledge and knowledge online require integration and simplification so that users get it with quality and quantity that is valid, accountable and according to the needs of the users themselves. Sources of knowledge or reading are still needed, whether in face-to-face conventional libraries with librarian services or with online media, the web or online library links. Hybridization of the two is still necessary according to the needs and character of the user concerned.